Clinical nursing pathway improves the nursing satisfaction in patients with acute cerebral hemorrhage: A randomized controlled trial protocol. Issue 44 (30th October 2020) - Fu, Su; Han, Hui; Fan, Chaofeng; Jiang, Yan
Abstract: Background: Cerebral hemorrhage (CH) is a very common cerebrovascular disorder in clinical practice. More and more studies reported that proper nursing care could promote the rate of treatment, and improve the prognosis after treatment. Clinical nursing pathway (CNP) refers to original nursing mode with good quality, outstanding efficiency, and low treatment spending. Few articles have reported the effect of CNP in patients with acute CH. The program is in urgent need of convinced evidence to prove the reliability. Thus, we perform this randomized controlled trial protocol and hypothesize that CNP is associated with improved outcomes and nursing satisfaction, reduced adverse reactions in patients with acute CH. Method: It is a single-center randomized controlled study to be conducted from October 2020 to October 2021. It was admitted via the Ethics Committee of the West China Hospital of Sichuan University (0038842/121). Eighty patients meet diagnostic standards for CH are included. The study group receives the clinical nursing path model. In the control group, patients receive the routine care before and after taking to the hospital. The main outcome contains the Barthel index score, the patient's degree of satisfaction about care, the length of hospital stay, and the risk of complications such as infection, bedsores and gastrointestinal function between the 2 groups. Six months after admission, the functional independence measure and Fugl Meyer score are recorded. All data are analyzed by the IBM SPSS Statistics, version 20 (IBM Corp., Armonk, NY edition). Results: Table 1 shows the clinical outcomes between groups. Conclusion: CNP may improve the clinical outcomes for patients with acute CH and have a significant value in actual applications. Trial registration number: researchregistry6061